Landscape Design Criteria in The Development of Healing Gardens (Ecological Perspective, 2025)
This study comprehensively examines how healing gardens are planned within the framework of landscape design principles, their design criteria, and the positive effects of these special spaces on health. Healing gardens are designed as multifunctional areas that integrate natural elements, sensory stimuli, sustainability, and user-centered accessibility principles to support physical, mental, and social well-being. In the design process, balancing privacy, social interaction, and sensory experiences while considering the needs of different user groups is of great importance.Selected exemplary healing garden projects from both global and Turkish contexts are analyzed within the scope of the study, evaluating their contributions to health-oriented design approaches in landscape architecture at local and international levels. Projects such as medicinal and aromatic plant gardens in Turkey exemplify how the concept of healing gardens integrates with education, therapy, and sustainable landscape practices.In conclusion, healing gardens hold a significant place in health-themed applications of landscape architecture, and the proliferation of such spaces will positively enhance user experience and public health. The adoption of sustainable and user-focused design approaches will increase the effectiveness of landscape projects in the health sector.
Keywords: Healing Garden; Therapeutic Garden; Landscape Design; Sustainable Landscape; Healthcare Spaces; Sensory Design